Post COVID‐19 condition diagnosis: A population‐based cohort study of occurrence, associated factors, and healthcare use by severity of acute infection. (7th December 2022) - Hedberg, Pontus; Granath, Fredrik; Bruchfeld, Judith; Askling, Johan; Sjöholm, Daniel; Fored, Michael; Färnert, Anna; Naucler, Pontus
Abstract: Background: The occurrence and healthcare use trajectory of post COVID‐19 condition (PCC) is poorly understood. Our aim was to investigate these aspects in SARS‐CoV‐2‐positive individuals with and without a PCC diagnosis. Methods: We conducted a population‐based cohort study of adults in Stockholm, Sweden, with a verified infection from 1 March 2020 to 31 July 2021, stratified by the severity of the acute infection. The outcome was a PCC diagnosis registered any time 90–360 days after a positive test. We performed Cox regression models to assess baseline characteristics associated with the PCC diagnosis. Individuals diagnosed with PCC were then propensity‐score matched to individuals without a diagnosis to assess healthcare use beyond the acute infection. Results: Among 204, 805 SARS‐CoV‐2‐positive individuals, the proportion receiving a PCC diagnosis was 1% among individuals not hospitalized for their COVID‐19 infection, 6% among hospitalized, and 32% among intensive care unit (ICU)–treated individuals. The most common new‐onset symptom diagnosis codes among individuals with a PCC diagnosis were fatigue (29%) among nonhospitalized and dyspnea among both hospitalized (25%) and ICU‐treated (41%) individuals. Female sex was associated with a PCC diagnosis among nonhospitalized and hospitalized individuals, with interactions between age and sex. Previous mental health disorders and asthma were associated with a PCC diagnosis among nonhospitalized and hospitalized individuals. Among individuals with a PCC diagnosis, the monthly proportion with outpatient care was substantially elevated up to 1 year after acute infection compared to before, with substantial proportions of this care attributed to PCC‐related care. Conclusion: The differential association of age, sex, comorbidities, and healthcare use with the severity of the acute infection indicates different trajectories and phenotypes of PCC, with incomplete resolution 1 year after infection. Abstract :